“It’s in Their Blood”. The Securitization of Roma Westward Migration in Europe - Anghel, Ionuţ-Marian (Calitatea Vieții, 2019)
If recent debates have centered around the irregularization and border securitization against non-EU migrants in the EU (Jansen et al., 2015), especially in the context of the “refugee crisis”, less attention is paid to the irregularization of migration of EU citizens, such as Europe’s Roma minorities (van Baar, 2014a; van Baar, 2015). The paper aims to critically interrogate the processes of securitization, irregularization, criminalization and nomadization of recent Roma westward migration in Europe. By discussing the cases of France and Italy’s “securitization packages”, I will show that the “excessive mobility” of Central and Eastern Europe (CEE) Roma is not the result of their alleged nomadic lifestyle but rather the outcome of policies of expulsion and “voluntary return schemes” put in place by Western governments. These policies reinforce the status of “third-country nationals” for the CEE Roma (although they are citizens of EU member states) and deepens the socio-political exclusion at a time when the European Commission (EC) and member states have put in place social inclusion policies that should have enhanced their European citizenship.